Kesesuaian tanah baki bagi biodegradasi sianida - Mohd Raihan Taha,; Nik Norsyahariati Nik Daud,; Wan Norita Merican, (2004)
A study to assess the suitability of residual soil as a medium for biodegradation processes for cyanide is presented in this paper: The residual soils we obtained from Universiti Kebangsaan Malaysia (UKM) in Bangi (granite residual soil), and Hospital Universiti Kebangsaan Malaysia (HUKM) in Cheras (sedimentary residual soil). The cyanide contaminated soils were bio-treated using the slurry phase or leachate method. Sampels were also mi.xed with a nutrient solution and innoculated with bacteria that has been breaded in the cyanide contaminated soil. These samples were tested in two environments, i.e.normal nutrient and catalystic (glucose) nutrient. The time allowed for the biodegradation processes was 78 hours. Results showed that HUKM residual soil have.a better characteristics for biodegradation processes compared to UKM residual soil. This is due to greater organic carbon, organic content and acidity of the HUKM residual soil that enhances biodegradation processes